ICTs in The Graduate Profile of Law Schools in Public and Private Universities In Peru: A Qualitative Research - Hugo GONZÁLEZ (Communications of International Proceedings, 2022)
This study analyzes the ICT-related categories that have been explicitly included in the graduate profiles of law schools in Peruvian universities. In this context, only thirteen universities have mentioned ICT in their profiles through their websites. The categories include: communication skills, practice of values, information search, critical use of technology, problem solving, use of technology in research, and professional performance. The most prevalent are research and job performance involving the use of technology.
Keywords: ICT; research; problem solving; professional performance; practice of values; communication skills.